OTFS-BOC: A novel signal modulation scheme for next-generation LEO satellite navigation services - Zhang, Tianci; Lu, Xiangchen; Cai, Lanbo; Shen, Yuyao; Ma, Zhifeng (Journal of physics. Conference series, 2025)
In doubly dispersive delay-Doppler channels, orthogonal frequency division multiplexing (OFDM)-based navigation signals suffer from degraded performance due to subcarrier orthogonality loss. To address the reduced energy concentration of orthogonal frequency division multiplexing with binary offset carriers (OFDM-BOC) signals under such conditions, this paper proposes a novel orthogonal time frequency space with binary offset carriers (OTFS-BOC) system that combines OTFS modulation with spread-spectrum BOC signaling, leveraging the superior robustness of orthogonal time frequency space (OTFS) against channel dispersion. A unified modulation and demodulation model is developed, along with practical implementation strategies for different application scenarios. Simulation results demonstrate improved ranging accuracy and transmission performance over OFDM-BOC, confirming the proposed system’s advantages in challenging environments.